Crossed Aphasia and Visuo-Spatial Neglect Following a Right Thalamic Stroke: A Case Study and Review of the Literature - Lieve De Witte; Jo Verhoeven; Sebastiaan Engelborghs; Peter P. De Deyn; Peter Mariën (Behavioural Neurology)
Crossed aphasia in dextrals (CAD) following pure subcortical lesions is rare. This study describes a right-handed patient with an ischemic lesion in the right thalamus. In the post-acute phase of the stroke, a unique combination of ‘crossed thalamic aphasia’ was found with left visuo-spatial neglect and constructional apraxia. On the basis of the criteria used in Mariën et al. [67], this case-report is the first reliable representative of vascular CAD following an isolated lesion in the right thalamus. Furthermore, this paper presents a detailed analysis of linguistic and cognitive impairments of ‘possible’ and 'reliable' subcortical CAD-cases published since 1975. Out of 25 patients with a pure subcortical lesion, nine cases were considered as ‘possibly reliable or reliable’. A review of these cases reveals that: (1) demographic data are consistent with the general findings for the entire group of vascular CAD, (2) the neurolinguistic findings do not support the data in the general CAD-population with regard to (a) the high prevalence of transcortical aphasia and (b) the tendency towards a copresence of an oral versus written language dissociation and a ‘mirror-image’ lesion-aphasia profile, (3) subcortical CAD is not a transient phenomenon, (4) the lesion-aphasia correlations are not congruent with the high incidence of anomalous cases in the general CAD-population, (5) neuropsychological impairments may accompany subcortical CAD.